2016
DOI: 10.1371/journal.pone.0161919
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation in Effects of Upwelling on the Fatty Acid Composition of Benthic Filter Feeders in the Southern Benguela Ecosystem: Not All Upwelling Is Equal

Abstract: Variability in mesoscale nearshore oceanographic conditions plays an important role in the distribution of primary production and food availability for intertidal consumers. Advection of nutrient rich waters by upwelling usually allows the proliferation of diatoms, later replaced by dinoflagellates. We examined upwelling effects on the fatty acid (FA) signature of a benthic intertidal filter feeder to identify its response to pulsed variability in food availability. The study took place in two contrasting seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 86 publications
(100 reference statements)
1
10
1
1
Order By: Relevance
“…In this case, L2 listeners should always respond faster to literal meaning, as it is generally more salient for L2 listeners. While our L2 results also produced this general effect, it is repeated in our L1 findings—something we would not expect if we assume that L1 listeners should often find the figurative meaning to be more salient (Giora, 1997 , 2002 ). While the availability of meaning does confirm that literal constituent meaning plays a role in processing idioms, we are not prepared to assume a necessary priority.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this case, L2 listeners should always respond faster to literal meaning, as it is generally more salient for L2 listeners. While our L2 results also produced this general effect, it is repeated in our L1 findings—something we would not expect if we assume that L1 listeners should often find the figurative meaning to be more salient (Giora, 1997 , 2002 ). While the availability of meaning does confirm that literal constituent meaning plays a role in processing idioms, we are not prepared to assume a necessary priority.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, both familiarity (see e.g., Libben and Titone, 2008 for an overview) and a strongly biasing figurative context (Colombo, 1993 ; Cacciari et al, 2007 ; Cacciari and Corradini, 2015 ) have been shown to affect access to figurative meaning. In fact, Giora ( 1997 , 2002 ) suggests that saliency—conventionality, frequency, familiarity, contextually supported—rather than an individual factor is most relevant in idiomatic processing. Instead of differentiating between literal and non-literal processing, she separates salient processing from non-salient processing: Saliency facilitates processing as salient meanings are retrieved immediately and directly, while non-salient meanings are retrieved through default language processing and integration processes.…”
Section: Introductionmentioning
confidence: 99%
“…The supply of omega-3 is expected to change in the near future as a consequence of climate change (e.g., Hixson and Arts, 2016;Colombo et al, 2020), with implications for meeting the omega-3 requirements of a growing human population that is predicted to reach 11 billion by 2100 (Roser, 2013). Major climate-driven factors relevant to omega-3 production include warming (Hixson and Arts, 2016), ocean acidification (Dörner et al, 2020), and variability in upwelling intensity (Puccinelli et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The Southern Caribbean Sea, and particularly the northeastern coast of Venezuela, is under the influence of coastal upwelling (Okuda et al, 1978;Jury, 2018). The high concentrations of nutrients during particular periods of the year stimulates the productivity of phytoplankton, and it has been hypothesized that the cycles of upwelling and relaxation (non-upwelling) modulate the availability of planktonic food for some benthic species, influencing, in turn, their growth patterns (Puccinelli et al, 2016). The predominant trade winds blow parallel to the coast and the topography of the continental shelf favor the upwelling of sub-tropical waters rich in nutrients, with a seasonal intensification between December and April (Müller-Karger and Aparicio-Castro, 1994, Freites et al, 2017) Recently, Rueda-Roa et al (2018 showed the presence of a mid-year upwelling cycle (June-August) in the northeastern coast of Venezuela, attributed to the intensification of the Caribbean Current during this period.…”
Section: Introductionmentioning
confidence: 99%